ARS and local wares from a late antique site in the Bay of Naples: Import, imitation, and market segments - Martucci, Caterina Serena; Castaldo, Vincenzo; De Simone, Girolamo Ferdinando (Rei Cretariae Romanae Fautorum Acta, 2022)
This paper studies the African Red Slip ware and its imitations from the Roman villa with baths in Pollena Trocchia. The site lies on the slopes of Mt. Vesuvius, in the ancient territory of Naples, and provides one of the largest datasets for late antique Campania. The ARS is 12 % of the entire assemblage and one third of the tableware. Hayes forms 61 and 91 are the most common types in both ARS and its imitations. Overall the assemblage shows strict similarities with the evidence in Naples, although less variety is noted among the types. In the final part, this contribution suggests that ARS and its imitations covered a specific market segment, rather than complementing the local products and provides a workingk hypothesis of a multi-layered distribution system.